RANCANG BANGUN SISTEM INFORMASI PENJUALAN BERBASIS CLOUD BAGI USAHA KECIL DAN MENENGAH DI INDONESIA (Studi Kasus: Toko Toko Besar) - Himawan, Stevanus C. M. H.; Wurijanto, Tutut; Sutanto, Teguh (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2013)
Small and Medium Enterprises (SMEs) have a huge effect on the economy and empowerment of labor in Indonesia. This is proven by the number of GDP produced by 56.5 % and labor absorption up to 97 % (Yoga; 2011). Nevertheless, the development of SMEs is still hampered by the lack of market knowledge and information. Currently, the information obtained was limited to the number of SMEs sales and earnings based on recap of transactions. SMEs cant get information about sales trend to find out the products being in demand, current stock information to determine reorder time to supplier, transaction history of customers and suppliers to find out their main customer and supplier. This information is needed by management to make a business decision. From all problems above, the authors will make a sales information system to record sales transactions and generate reports of sales trends, current stock and transaction history of customers and suppliers. The sales information system use cloud computing technology so that SMEs do not have to provide a huge investment to purchase their own infrastructure and maintenance costs. The system can also be accessed anytime and anywhere through the internet. Thus, the management can get sales information wherever they are, and decision making can be helped by current information produced by the system. Keywords: Sales Information System, Small and Medium Enterprises, Cloud Computing